2019
DOI: 10.1186/s12544-019-0382-4
|View full text |Cite
|
Sign up to set email alerts
|

Preventing the risks of monotony related fatigue while driving through gamification

Abstract: Background: Driving fatigue can have serious consequences. Too often fatal accidents are caused by fatigue. However, it is not uncommon for fatigue to occur while driving when the driver is under-challenged. Due to the increasing automation of vehicles, it is foreseeable that the number of accidents caused by monotony will increase. Interactions between driver and vehicle through gamification can remedy the situation and provide the driver with new stimuli during an otherwise monotonous journey. Methods: In or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 88 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…Thus, an intervention could be triggered that acts as a mental stimulus to increase arousal and thereby prevent drowsy driving. Past research developed and evaluated such interventions, for example, using highly personalized music playlists [ 21 ] or gamified driving challenges [ 75 ]. Our findings could pave the way for the ideation of new interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an intervention could be triggered that acts as a mental stimulus to increase arousal and thereby prevent drowsy driving. Past research developed and evaluated such interventions, for example, using highly personalized music playlists [ 21 ] or gamified driving challenges [ 75 ]. Our findings could pave the way for the ideation of new interventions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Repero-Padilla et al argue that the design of gamification elements in online learning environments, such as points, rewards, challenges, and leaderboards, is highly effective in enhancing students' interest, motivation, and persistence [34]. Additionally, Bier et al's research found that gamified interpersonal interaction systems can assist users in maintaining excitement and attention [35]. Hamari et al's study suggests that the effectiveness of gamification in regard to learning outcomes may vary in different contexts [21].…”
Section: Gamification and Learning Motivation In The Metaversementioning
confidence: 99%
“…During initial engagement of a goal-directed task, reinforcement learning occurs to favor reward-contingent behavior, and when the ACC detects non-conducive behavioral deviations (e.g., lapses in attention) the prefrontal cortex is recruited to exercise top-down control to calibrate behavior, by way of increasing LC phasic activity, to maintain optimal performance (Aston-Jones and Cohen, 2005 ; Sara and Bouret, 2012 ; Massar et al, 2016 ; Bier et al, 2019 ). As engagement in the task continues, the costs associated with optimal performance tend to increase, while the rewards associated with the task tend to decrease due to increased satiety, exposure, or predictability of the rewards, eventually resulting in increased LC tonic activity.…”
Section: Processes Underlying Passive Fatiguementioning
confidence: 99%
“…Similarly, when drivers interacted with a system that gamified driving and rewarded drivers for good performance (e.g., degree of lateral steering control, hazard avoidance, etc.) during a manual drive, subjective fatigue was delayed, standard deviation of lane position and unintentional lane crossings were reduced, drivers were less prone to accidents, and there was better compliance with driving at the speed limit (Bier et al, 2019 ). Rewards may be introduced to help rebalance a task's utility by fostering motivation and optimizing one's arousal state for the task at hand (Aston-Jones and Cohen, 2005 ; Boksem and Tops, 2008 ).…”
Section: Processes Underlying Passive Fatiguementioning
confidence: 99%
See 1 more Smart Citation